PERAN SISTEM INFORMASI AKUNTANSI DALAM MENDUKUNG KEPUTUSAN MANAJEMEN PADA PT PLN (PERSERO) UP3 MAKASSAR SELATAN - Alisya Putri; Chairul Ihsan Burhanuddin; muttiarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Alisya Putri. 105731110521. The Role of Accounting Information Systems in Supporting Management Decisions at PT PLN (Persero) UP3 South Makassar. Thesis, Department of Accounting, Faculty of Economics and Business, Muhammadiyah University of Makassar. Supervised by Chairul Ihsan Burhanuddin and Muttiarni. This study aims to analyze the accounting information system used to support management decision-making at PT PLN (Persero) UP3 South Makassar. This study used a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results show that the accounting information system used is integrated with the SAP (Systems, Applications, and Products) system, which supports the efficiency and effectiveness of financial information processing. This system plays a crucial role in recording, processing, and reporting financial information and serves as the primary basis for managerial decision-making. However, several obstacles remain, such as system disruptions and limitations in real-time data processing, which require attention to improve the quality of the information presented. Overall, the accounting information system at PT PLN UP3 Makassar Selatan strengthens transparency, accountability, and accuracy in management decision-making.